Effectiveness of a Telerehabilitative Home Exercise Program on Elder Adults' Physical Performance, Depression and Fear of Falling. Issue 3 (June 2022) - Tekin, Fatih; Cetisli-Korkmaz, Nilufer
Our aim in this study was to analyze the effects of a home exercise program of calisthenic exercises delivered through telerehabilitation on physical performance, depression, and risk of falling in elder adults. Our participants were elder adults aged 65 and over, divided into exercise and control groups. We initiated a 4-week telerehabilitation calisthenic exercise program in the exercise group following initial assessments, while our control group received no formal exercise training. Both groups were evaluated online before and after this 4-week period with the Geriatric Depression Scale (GDS), Modified Falls Efficacy Scale (MFES), and Short Physical Performance Battery (SPPB). In total, 255 elder adults participated, with 132 (males = 72, females = 60) allocated to calisthenic exercise and 123 (males = 66, females = 57) allocated to the control group. While the groups did not differ significantly on any of our parameters before the exercise, there were statistically significant post-exercise group differences in GDS ( p ≤ .001) and MFES ( p ≤ .001) scores related to remarkable physical improvements achieved in the calisthenic exercise group. The exercise group showed significant increases in their scores on the SPPB Balance Test ( p = .049), SPPB Chair Test ( p = .009), and SPPB Total ( p = .002) while there was no significant increase in any of these scores among control group participants ( p > .05). Thus, calisthenic exercises performed via telerehabilitation significantly improved elder adults' physical performance, fear of falling, and depression. Telerehabilitation is a useful remote means of assessing, inducing, and following-up exercise training, particularly during the ongoing COVID-19 pandemic.